Sunny side up - Holm, Jennifer L.; Holm, Matthew (Graphix, an imprint of Scholastic, 2015)
Sunny Lewin is sent to live with her grandfather for the summer in Florida, where she befriends Buzz, a boy completely obsessed with comic books, and faces the secret behind why she is in Florida in the first place.